Sincerity (iskrennost) vs. Candour (shchirist): Cultural and Historical Semantics of the Word in the Closely-Related Languages - Савченко, Людмила Ростиславівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The meanings of the Russian word iskrennost, which nominates a nationality-specific communicative category, is contrasted with its Ukrainian correlative shchirist in the article. The study suggests that the historical link with different languages as sources leads to the peculiarities of the meanings as well as the nature of their semantic derivation.